Survival as a clinical outcome and its spiritual significance in a cohort of patients with advanced central pelvic neoplastic disease undergoing total pelvic evisceration: a poorly debated issue - Macciò, Antonio; Sanna, Elisabetta; Piras, Roberta; Lavra, Fabrizio; Vallerino, Valerio; Maricosu, Giovanni; Giglio, Emanuela; Mura, Antonio; Tidore, Marcello; Madeddu, Clelia (Frontiers in Medicine, 2023)
Background: Patients with advanced central pelvic neoplastic disease present with a condition responsible for debilitating symptoms and poor quality of life (QoL). Total pelvic evisceration can be the only option to relief symptoms and increase survival. Patients and methods: This study aimed to prospectively evaluate the improvement in survival and QoL, focusing on spiritual well-being (SWB), in patients who underwent total pelvic evisceration for advanced gynecological cancers with poor life expectancy at our center. QoL and SWB were assessed by validated questionnaires administered 30 days before surgery, 7 days, 1 month, and 3 months after surgery, and then every 3 months until death or last follow-up assessment. The patients and their families were included in a dedicated psycho-oncological and spiritual support protocol, managed by specifically trained personnel during all phases of the study. Results: From 2017 to 2022 we included 20 consecutive patients: 7 underwent total pelvic evisceration by laparotomy and 13 by laparoscopy. Median survival was 24 months (range 1-61 months). After a median follow-up of 24 months, 16 patients (80%) were alive at 1 year, and 10 patients (50%) were alive at 2 years after surgery. The EORTC-QLQ-C30 improved significantly yet at 7-day, and at 1 month, 3, 6, and 12 months in comparison to values before surgery; in particular, an early improvement of pain, overall QoL, physical, and emotional function was observed. As regard SWB, the global SWB item of the EORTC QLQ-SWB32 increased significantly after 1 month and 3 months compared with value before surgery, and remained stable thereafter. The SWB scale at baseline reported a sense of low overall SWB in ten patients, moderate SWB in eight patients, and high SWB in two patients. The SWB scale score increased significantly after 7 days, 1 month, and 3 months in comparison to preoperative value, and remained stable thereafter. Conclusion: Total pelvic evisceration represents a valid approach for improving both survival ad QoL in selected patients with advanced pelvic neoplasms with a poor life expectancy. Our results underline the importance of accompanying the patients and their families during the journey with dedicated psychological and spiritual support protocols.